ANALISIS PENGARUH PENGETAHUAN, STRUKTUR MODAL, TERHADAP KINERJA SAHAM SYARIAH DALAM PERSPEKTIF ISLAM DENGAN PENDEKATAN CIRCULAR CAUSATIONDI BURSA EFEK INDONESIA - Hotman Tohir Pohan (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2015)
This study aims to determine the influence of knowledge and capital structure to the sharia stock performance in Islamic perspective with circular causation approach in the Indonesia Stock Exchange. This is a descriptive study to test the hypotheses of causality. The sample size is calculated by using the Slovin formula, and the Partial Least Square is used for data analysis and hypothesis testing. The results of this study indicate that the sharia stock performance is significantly and positively influenced by knowledge mediated by the capital structure. There is no effect of capital structure on the sharia stock performance mediated by knowledge; there is a significantly positive effect of knowledge on the capital structure mediated by the sharia stock performance; there is no effect of the sharia stock performance on the capital structure mediated by knowledge; there is a significantly positive effect of knowledge on the capital structure mediated by the sharia stock performance ; there is a significantly positive effect of knowledge on the sharia stock performance mediated by the capital structure. The unreal reciprocal effect exists only in the influence of capital structure to the sharia stock performance and the influence of the sharia stock performance to the capital structure. Key Word: Knowledge, Circular Causation